2022
DOI: 10.3389/fonc.2022.1004978
|View full text |Cite
|
Sign up to set email alerts
|

The magic bullet: Niclosamide

Abstract: The term ‘magic bullet’ is a scientific concept proposed by the German Nobel laureate Paul Ehrlich in 1907, describing a medicine that could specifically and efficiently target a disease without harming the body. Oncologists have been looking for a magic bullet for cancer therapy ever since. However, the current therapies for cancers—including chemotherapy, radiation therapy, hormone therapy, and targeted therapy—pose either pan-cytotoxicity or only single-target efficacy, precluding their ability to function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 172 publications
(248 reference statements)
1
21
0
Order By: Relevance
“…Reversing the Warburg effect might be an approach to restore cell differentiation in cancer. Haowen Jiang et al used a mitochondrial uncoupler, niclosamide ethanolamine (NEN), to activate mitochondrial respiration, which induced neural differentiation in neuroblastoma cells [ 42 ]. The results suggest that mitochondrial uncoupling is an effective metabolic and epigenetic therapy for reversing the Warburg effect and inducing differentiation in neuroblastoma.…”
Section: Mitochondrial Dysfunction and Ncdsmentioning
confidence: 99%
“…Reversing the Warburg effect might be an approach to restore cell differentiation in cancer. Haowen Jiang et al used a mitochondrial uncoupler, niclosamide ethanolamine (NEN), to activate mitochondrial respiration, which induced neural differentiation in neuroblastoma cells [ 42 ]. The results suggest that mitochondrial uncoupling is an effective metabolic and epigenetic therapy for reversing the Warburg effect and inducing differentiation in neuroblastoma.…”
Section: Mitochondrial Dysfunction and Ncdsmentioning
confidence: 99%
“…Thus, alternative approaches targeting the proteostatic adaptations within MM cells will bring clinical bene t. Niclosamide (NIC) is a well-tolerated oral anti-helminthic drug used to treat parasitic infections worldwide(28). NIC has also been demonstrated to have potential anti-tumour activity against multiple cancers (reviewed in (29)(30)(31)(32)) and we previously demonstrated the anti-MM activity of NIC (33). Due to poor aqueous solubility, NIC has limited oral bioavailability and other groups have sought to modify its structure/delivery to improve solubility (31,34,35).…”
Section: Introductionmentioning
confidence: 98%
“…NIC has also been demonstrated to have potential anti-tumour activity against multiple cancers (reviewed in (29)(30)(31)(32)) and we previously demonstrated the anti-MM activity of NIC (33). Due to poor aqueous solubility, NIC has limited oral bioavailability and other groups have sought to modify its structure/delivery to improve solubility (31,34,35). We reasoned that an alternative, faster strategy is to seek adjuvant therapies that potentiate the anti-MM activity of standard NIC at currently achievable safe serum concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Niclosamide is an FDA‐approved anthelmintic drug for the treatment of parasitic infections (Figure 1A). 9 Beyond this anti‐helminthic activity, niclosamide also exhibits anticancer properties by inhibiting oncogenic pathways and activating tumor suppressor signaling pathways 10 . In addition, there are many studies in which niclosamide was combined with different agents 10 .…”
Section: Introductionmentioning
confidence: 99%
“… 9 Beyond this anti‐helminthic activity, niclosamide also exhibits anticancer properties by inhibiting oncogenic pathways and activating tumor suppressor signaling pathways 10 . In addition, there are many studies in which niclosamide was combined with different agents 10 . Akgun et al showed that niclozamide inhibited the Wnt/β‐Catenin pathway, which has a role in the EMT process, and that its combinations with histone deacetylase inhibitor valproic acid had a synergistic effect to kill lung cancer cells 11 …”
Section: Introductionmentioning
confidence: 99%